MEMBANGUN SINERGI ANTARA MUTU, PRODUKSI, DAN KUALITAS IKAN TONGKOL : TINJAUAN LITERATUR - Emia Rehulina Br Bangun; Sukma Rakha Az-Zahra; Hanakayda Khairunnisa; Fany Apriliani (CV. KAMPUS AKADEMIK PUBLISING, 2024)
Tuna (Euthynnus Affinis) is a capture fisheries commodity with the highest production in 2022 in marine waters of 160.727 thousand tons (Ministry of Marine Affairs and Fisheries). To get the best tuna requires synergy between quality, production activities and quality of tuna. This journal provides an overview of the 3 main keys of tuna. The method used is the literature study method or literature study by collecting various international and national journals. The stages of analyzing various journals start from collecting, filtering journals that are relevant to the title, understanding and presenting the results in the form of a critical review. The purpose of writing this journal is to identify appropriate post-harvest handling to maintain the quality standards and quality of tuna, to identify challenges and obstacles in building synergies between the quality, production, and quality of tuna products, and to determine the role of fishermen, processing industry and government in building synergies between the quality, production process, and quality of tuna products The results of the critical review are in the form of determining the quality standards of tuna commodities, the production process of tuna, and the quality of tuna expected by consumers so that they can meet the needs of consumers